대면 서비스직 종사자의 COVID-19 스트레스, 정량뇌파 스트레스 지수와 대처방식의 상관분석 - 원희욱; 손해경 (한국직업건강간호학회지, 2021)
Purpose: This study aimed to measure COVID-19 stress and the quantitative electroencephalography (QEEG) stress quotient and identify the coping styles of face-to-face service industry employees during the COVID-19 pandemic. Methods: This cross-sectional study administered structured questionnaires consisting of sections on general characteristics, COVID-19 stress, and coping style for stress to 21 face-to-face service industry employees between April 1 and April 18, 2021. The physical tension & stress quotient and psychological distraction & stress quotient were measured in the prefrontal lobe with QEEG. Results: Emotional easiness (r=.62, p=.002) and escape-avoidance (r=.55, p=.009) as a passive coping style were associated with COVID-19 stress, and seeking social support as an active coping style was associated with the left physical tension & stress quotient (r=.47, p=.031). Conclusion: These findings provide evidence regarding the objective status of the mental health of face-to-face service industry employees using both a self-reported scale and neuroscientific indicators, including brain quotients.